Global politics a new introduction - Edkins, Jenny; Zehfuss, Maja (Routledge, 2014)
Provide a completely original way of teaching and learning about world politics. The book engages directly with the issues in global politics that students are most interested in, helping them to understand the key questions and theories and also to develop a critical and inquiring perspective. Completely revised and updated throughout, the 2nd edition also offers additional chapters on key issues such as environmental politics, nationalism, the internet, democratization, colonialism, the financial crisis, political violence and human rights.